2013
DOI: 10.1080/00949655.2012.661431
|View full text |Cite
|
Sign up to set email alerts
|

A note on empirical likelihoods derived from pairwise score functions

Abstract: Pairwise likelihood functions are convenient surrogates for the ordinary likelihood, useful when the latter is too difficult or even impractical to compute. One drawback of pairwise likelihood inference is that, for a multidimensional parameter of interest, the pairwise likelihood analogue of the likelihood ratio statistic does not have the standard chi-square asymptotic distribution. Invoking the theory of unbiased estimating functions, this paper proposes and discusses a computationally and theoretically att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Other approaches, invoking the theory of unbiased estimating functions, have been suggested to produce likelihood ratio‐type statistics that allow reference to the usual asymptotic chi‐squared distribution (Lunardon et al, ; Lunardon & Ronchetti, ). However, in contrast to the proposed likelihood ratio‐type statistic, which directly adjusts the scoring rule itself, these tests are derived from an unbiased estimating function for which a convex function to be used in the likelihood ratio‐type statistics is usually unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches, invoking the theory of unbiased estimating functions, have been suggested to produce likelihood ratio‐type statistics that allow reference to the usual asymptotic chi‐squared distribution (Lunardon et al, ; Lunardon & Ronchetti, ). However, in contrast to the proposed likelihood ratio‐type statistic, which directly adjusts the scoring rule itself, these tests are derived from an unbiased estimating function for which a convex function to be used in the likelihood ratio‐type statistics is usually unavailable.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we outline that the proposed method can be extended to other types of data and to the space time setting using spatio-temporal blocks (Kleiber & Porcu (2014); Martinez-Ruiz et al (2010); Ruiz-Medina et al (2008); Yu et al (2007)). In addition to that, differently from standard likelihood methods, it is well-known that the PL likelihood ratio test does not have a standard limiting distribution (Lunardon et al (2012); Pace et al (2011)). On the other hand, it could be shown that EU-based tests are chi square distributed.…”
Section: Discussionmentioning
confidence: 98%
“…See also Caragea & Smith (2006), Fuentes (2007), Lindsay (1988), Stein (2008), Stein et al (2004) and Vecchia (1988). Lunardon et al (2012), in the IID case, use empirical likelihood (EL) with moment conditions coming from the score function of the PL in order to overcome the problem of non standard asymptotic distribution of the likelihood ratio statistic of the PL. See also Qin & Lawless (1994) for a general reference on EL estimation for moment condition models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative we introduce another test, which has the appeal that there is no need to compute the Godambe information matrix. This test is based on the empirical likelihood framework, which in the context of CML estimation was first used by Lunardon et al (2013) to derive confidence regions for CML estimates. Using general results from Qin and Lawless (1994) it is straightforward to also introduce a likelihood-ratio-like test for CML.…”
Section: Likelihood-ratio-type Testsmentioning
confidence: 99%